2004
DOI: 10.1111/j.1365-3156.2004.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ivermectin on illness and disability associated with onchocerciasis

Abstract: SummaryThe Onchocerciasis Control Program (OCP), one of the most successful vertical disease control programs in the history of public health, came to an end in 2003 with devolvement of responsibilities for control program activities passed to the countries affected. Fortunately, 15 years ago the Mectizan Ò Distribution Program (MDP) was founded to provide a complementary approach to controlling the disabling consequences of this parasitic infection. With over 250 million doses of ivermectin distributed over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 89 publications
(170 reference statements)
1
37
0
Order By: Relevance
“…In fact, the 'beyond-lymphatic filariasis benefits' discussed within the Global Programme to Eliminate Lymphatic Filariasis, which delivered about 150 million ivermectin treatments, include a reduction of scabies, pediculosis, and soil-transmitted helminth infections in communities in which these diseases are endemic [65]. A reduction of the transmission of soil-transmitted helminth infections and scabies in affected communities has also been perceived as an additional benefit within the ivermectin-based Onchocerciasis Control Program [65][66][67]. Similarly in Nigeria, communities reported additional benefits of ivermectin mass treatment against onchocerciasis [68]: about one-fourth reported to have expelled intestinal helminths after treatment with ivermectin, 19% improved body itching, and 17% reduced skin rash possibly because of scabies; others reported clearance of head lice infestations [68].…”
Section: Specific Features Of Scabies Control In Endemic Communitiesmentioning
confidence: 97%
“…In fact, the 'beyond-lymphatic filariasis benefits' discussed within the Global Programme to Eliminate Lymphatic Filariasis, which delivered about 150 million ivermectin treatments, include a reduction of scabies, pediculosis, and soil-transmitted helminth infections in communities in which these diseases are endemic [65]. A reduction of the transmission of soil-transmitted helminth infections and scabies in affected communities has also been perceived as an additional benefit within the ivermectin-based Onchocerciasis Control Program [65][66][67]. Similarly in Nigeria, communities reported additional benefits of ivermectin mass treatment against onchocerciasis [68]: about one-fourth reported to have expelled intestinal helminths after treatment with ivermectin, 19% improved body itching, and 17% reduced skin rash possibly because of scabies; others reported clearance of head lice infestations [68].…”
Section: Specific Features Of Scabies Control In Endemic Communitiesmentioning
confidence: 97%
“…In endemic situations, empirical treatment is often more cost effective than laboratory-based testing, and recently mass intervention programs with ivermectin in Africa [11], Brazil [12], and the Solomon Islands [13] have resulted in dramatic reductions in the prevalence of onchocerciasis, filariasis, intestinal helminths, and scabies. Approximately 250 million doses of ivermectin have been distributed over 15 years for the treatment of onchocerciasis in a variety of African countries, and it appears to be a safe, highly-effective treatment with few adverse events reported.…”
Section: Chemotherapymentioning
confidence: 99%
“…Whereas the original Onchocerciasis Control Programme was initially focused on vector control, the current African Programme for Onchocerciasis Control (APOC) is almost entirely dependent on mass drug administration (MDA) of the macrocyclic lactone ivermectin (4). This strategy has been in place in many regions of endemicity for approximately 2 decades and has been extremely successful in preventing blindness and onchodermatitis (5), since ivermectin rapidly clears Mf from the skin. Recent data have also demonstrated that ivermectin can eliminate onchocerciasis in areas of seasonal transmission (6), and this has led APOC to redefine itself as an elimination program with a target attainment date of 2025 (4).…”
mentioning
confidence: 99%